東漢趙壹《非草書》作時考: A Critical Inquiry on the Written Time of Zhao Yi’s “Fei Cao Shu” in the Dung Han Dynasty - 馮, 翠兒 (人文中國學報, 2005)
<span data-sheets-value="{"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."}" data-sheets-userformat="{"2":705,"3":{"1":0},"9":0,"10":1,"12":0}" data-sheets-validation-definition="{"1":{"1":{"1":24,"2":[{"1":0,"5":{"1":{"1":0},"2":{"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."}}},{"1":0,"5":{"1":{"1":0},"2":{"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only."}}}]},"2":{"1":{"1":[{"1":4,"6":0},{"1":2,"3":"TRIM","4":1},{"1":3,"5":{"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."}},{"1":3,"5":{"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only."}},{"1":2,"3":"ARRAY_ROW","4":2},{"1":2,"3":"ARRAY_LITERAL","4":1},{"1":2,"3":"TRIM","4":1},{"1":2,"3":"EXACT","4":2},{"1":2,"3":"OR","4":1},{"1":2,"3":"ARRAYFORMULA","4":1},{"1":1,"2":"="}]},"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S"},"3":[{"1":{"1":0,"2":1,"3":0,"4":1,"5":1118464},"2":0}]},"2":"","3":0,"4":1}" data-sheets-validation-id="0">LANGUAGE NOTE | Document text in Chinese; abstract also in English. <span data-sheets-value="{"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."}" data-sheets-userformat="{"2":705,"3":{"1":0},"9":0,"10":1,"12":0}" data-sheets-validation-definition="{"1":{"1":{"1":24,"2":[{"1":0,"5":{"1":{"1":0},"2":{"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."}}},{"1":0,"5":{"1":{"1":0},"2":{"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only."}}}]},"2":{"1":{"1":[{"1":4,"6":0},{"1":2,"3":"TRIM","4":1},{"1":3,"5":{"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."}},{"1":3,"5":{"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only."}},{"1":2,"3":"ARRAY_ROW","4":2},{"1":2,"3":"ARRAY_LITERAL","4":1},{"1":2,"3":"TRIM","4":1},{"1":2,"3":"EXACT","4":2},{"1":2,"3":"OR","4":1},{"1":2,"3":"ARRAYFORMULA","4":1},{"1":1,"2":"="}]},"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S"},"3":[{"1":{"1":0,"2":1,"3":0,"4":1,"5":1118464},"2":0}]},"2":"","3":0,"4":1}" data-sheets-validation-id="0">東漢趙壹《非草書》一文在書法理論史上具有相當重要的地位，且對文學理論的影響也不小；但它的作時，至今仍未得到滿意的考證結論。故本文將結合東漢末年多件史實，推斷它的大概寫時和探索趙壹的寫作動機。希望後人在引用《非草書》時，不致產生偏頗，從而爲書論和文論的研究帶來點幫助。 The article “Fei Cao Shu” written by Zhao Yi of Dung Han is highly commended and has important influence on the theories of calligraphy and literature. However, when it was written remains doubtful, and there have not yet been some well-accepted proves. This article tries to draw together a number of historical facts in the late Dung Han Dynasty to deduce the approximate time when it was written and investigate Zhao Yi's written motives. The purpose is to eliminate possible bias when reference is made to “Fei Cao Shu", thus making some contribution to the studies of the theories of calligraphy and literature.